BAC-Pool Sequencing and Assembly of 19 Mb of the Complex Sugarcane Genome - Okura, Vagner Katsumi; Souza, Rafael S. C. de; de Siqueira Tada, Susely F.; Arruda, Paulo (Frontiers in Plant Science, 2016)
Sequencing plant genomes are often challenging because of their complex architecture and high content of repetitive sequences. Sugarcane has one of the most complex genomes. It is highly polyploid, preserves intact homeologous chromosomes from its parental species and contains >55% repetitive sequences. Although bacterial artificial chromosome (BAC) libraries have emerged as an alternative for accessing the sugarcane genome, sequencing individual clones is laborious and expensive. Here, we present a strategy for sequencing and assembly reads produced from the DNA of pooled BAC clones. A set of 178 BAC clones, randomly sampled from the SP80-3280 sugarcane BAC library, was pooled and sequenced using the Illumina HighSeq2000 and PacBio platforms. A hybrid assembly strategy (AHA) was used to generate 2,451 scaffolds comprising 19.2 MB of assembled genome sequence. Scaffolds of ≥20Kb corresponded to 80% of the assembled sequences, and the full sequences of forty BACs were recovered in one or two contigs. Alignment of the BAC scaffolds with the chromosome sequences of sorghum showed a high degree of collinearity and gene order. The alignment of the BAC scaffolds to the 10 sorghum chromosomes suggests that the genome of the SP80-3280 sugarcane variety is 19% contracted in relation to the sorghum genome. In conclusion, our data show that sequencing pools composed of high numbers of BAC clones may help to construct a reference scaffold map of the sugarcane genome.